Current methods of modeling depression in animals and approaches to the study of their efficiency in biomedical research (review of the problem) - D. S. Gromova; N. R. Popova; O. N. Pavlova; Yu. V. Myakisheva; S. I. Pavlenko (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Depressive disorders are one of the leading problems of modern health care. Their prevalence in the world ranges from 4.4 to 20 % of the population, and in Russia the incidence of depression reaches 20 %. The study of depressive disorders is relevant not only from the point of view of psychiatry and behavioral therapy, but also occupies a leading place in neurological practice, since more than a quarter of the population with chronic neurological diseases suffer from depression. Currently, most basic biomedical research on depressive disorders is carried out using laboratory animals. However, the protocols for experimental modeling and analysis of behavioral patterns are very diverse, which creates certain difficulties in planning research. This review is aimed at describing, analyzing, comparing and systematizing possible approaches to creating experimental models of depression in animals, and also contains criteria for model validation and a description of behavioral tests to assess anxiety-depressive disorders.